Subjetividade jurídica e trabalho: antagonismo e crítica nos marcos do capitalismo de plataforma - Felipin, Giovano José (2024)
This work presents a study on the contradictions and potentialities of the antagonism produced between modern legal subjectivity and the emerging new morphology of labor within the framework of platform capitalism. To this end, it utilizes historical-dialectical materialism to determine the real abstractions and the trend movement of the capital-labor relationship in contemporary times. Divided into two chapters, each segmented into two subchapters, the research investigates the relationships between law, labor, and subjectivity in post-Fordist capitalist sociability, articulated through a neoliberal algorithmic rationality. The first chapter addresses the legal form and labor as categories in contemporary capitalist sociability, their contradictions, and potentialities. The second chapter examines the elements for an antagonistic understanding of law in platform capitalism. In this sense, regulation theory and operaism are employed to understand the relationships between legal form, development mode, and cycles of struggle between technical composition and political recomposition of the working class today. In conclusion, it politically reflects on the locus of law in the constitutive relationship between capital and labor in contemporary times, sometimes as catastrophe, sometimes as transformation.